2008
DOI: 10.1002/pbc.21544
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the neuropsychological sequelae of chemotherapy‐only treatment for pediatric acute lymphoblastic leukemia

Abstract: Results support the presence of neuropsychological and academic sequelae for ALL survivors treated solely with chemotherapy and highlight the need for ongoing follow-up of children with ALL using a standardized neuropsychological test battery and research methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
155
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(173 citation statements)
references
References 31 publications
14
155
0
4
Order By: Relevance
“…Our findings are consistent with those of a recently published study that found over 90% of Latino parents of childhood cancer survivors expressed interest in a culturally competent intervention aimed at reducing neurocognitive late effects [9]. Our intervention is based on the premise that neurocognitive assessment should be a standard component of survivorship care for at-risk patients, and that it plays a crucial role in addressing immediate school needs, as well as longer-term educational, vocational, and employment outcomes [2][3][4]10]. We believe that the critical ingredient of our approach is its culturally competent design and implementation (Table S1), which includes a culturally and linguistically competent psychologist.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings are consistent with those of a recently published study that found over 90% of Latino parents of childhood cancer survivors expressed interest in a culturally competent intervention aimed at reducing neurocognitive late effects [9]. Our intervention is based on the premise that neurocognitive assessment should be a standard component of survivorship care for at-risk patients, and that it plays a crucial role in addressing immediate school needs, as well as longer-term educational, vocational, and employment outcomes [2][3][4]10]. We believe that the critical ingredient of our approach is its culturally competent design and implementation (Table S1), which includes a culturally and linguistically competent psychologist.…”
Section: Discussionsupporting
confidence: 80%
“…Although approximately 90% of patients become long-term survivors, up to 40% may develop treatment-related neurocognitive dysfunction that impairs learning and school performance [1][2][3]. Consequently, routine neuropsychological screening is recommended by the Children's Oncology Group (COG Long-Term Follow-Up Guidelines) for all childhood ALL survivors [4].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Individual studies in the past have shown some negative effects of treatment. However, most of these studies were hindered by small sample size and lack of appropriate controls, which makes it challenging to interpret and generalize their findings.11-14 Conclusions from systematic reviews have been mixed, [16][17][18] largely because of reliance on qualitative methods to assess outcomes 18 and inclusion of studies with patients who had very recently completed therapy or without a control population. [16][17][18] Because neurocognitive impairment takes time to develop and/or be detected, early assessments are likely not adequate.…”
mentioning
confidence: 99%
“…6 Therefore, the effect of different therapies on future quality of life has increasingly been considered as a critical factor in the selection of optimal treatment. Multiple previous studies of long-term survivors of childhood ALL, even those who did not receive cranial radiation, [7][8][9][10][11][12] have identified deficits in neurocognitive function that might impair quality of life. Among others, investigators have consistently identified difficulties in attention, working memory, processing speed, mathematics, and visual motor integration, but the exact etiologic factors of these deficits have not yet been established.…”
Section: Introductionmentioning
confidence: 99%